Sex Work, Sensory Urbanism and Visual Criminology: Exploring the Role of the Senses in Shaping Residential Perceptions of Brothels in Blackpool. (1st March 2018) - Cooper, Emily; Cook, Ian R.; Bilby, Charlotte
Abstract: Urban studies and criminology have much to offer each other, but the links between the two have so far been underexplored. This article is an illustration of how aspects of both can, and should, be brought into conversation: namely the literatures on sensory urbanism (in urban studies) and visual criminology. The benefits of doing so are evidenced by a case study exploring the ways in which the senses shape residents' perceptions of brothels in Blackpool. Three key findings emerge from the case study. First, the residents interviewed tended to focus on the visual aspects of brothels rather than other sensory aspects. Nevertheless, touch and smell (and their interaction with the visual) also played small but important roles in shaping residential perceptions. Second, residential perceptions of sex work and brothels are linked to, and encompass, a plurality of emotional responses. Third, while the residents could see or hear little of what was happening inside the brothels, they often sought out sensory clues from outside, typically drawn from the architectural features of the brothels. Such insights, we argue, are made possible by, and highlight the possibilities of, the bringing together of urban studies and criminology.